Wakaf infrastruktur menurut perspektif hadith dan aplikasinya dalam pembangunan hartanah wakaf di Selangor / Mohd Ashrof Zaki Yaakob - Mohd Ashrof Zaki , Yaakob (2018)
The practices of waqf infrastructure by the Prophet SAW and the companions RA represent the main reference and guidance for muslims in the continuation of current waqf implementation. This study attempts to analyze the hadith of waqf infrastructure in al-Kutub al-Sittah and its discussion through fiqh al-hadith. The study also scrutinizes the fiqh discussion among the Islamic jurists on property and ownership of waqf properties in the implementation of waqf infrastructure, and also analyzing transformation in waqf administration and management in Selangor. The development of waqf infrastructure by Perbadanan Wakaf Selangor (PWS) is compared with waqf infrastructure development based on the hadith perspective and hence, a guideline on the implementation of waqf infrastructure based on hadith be developed. To achieve these objectives, this study employs library research and interviews for data collection methods. The findings showed that there are 27 texts of the hadith waqf infrastructure in the al-Kutub al-Sittah which comprises of three major categories: religious infrastructure, public utilities infrastructure and infrastructure in general. From the fiqh perspectives, the findings ascertain a close relationship between the concept of property and property ownership for waqf infrastructure. Analysis of both waqf infrastructure developments from PWS and hadith in the al-Kutub al-Sittah reveal that there is similar yet not parallel infrastructure development. Based on the overall analysis and findings of this study, a guideline and a model for waqf infrastructure development are therefore suggested according to the perspective of hadith. It is expected that the findings of this study could be made as references for those involve in administration and management of waqf in Malaysia.